(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
Due to the depletion of petroleum reserves and environmental concern, biodiesel has emerged as one of the most potential energy to replace petroleum. It is a renewable, biodegradable and non-toxic fuel which can be easily produced through transesterification. Transesterification of palm oil with methanol has been studied in a homogenous catalyst system using different catalysts (CaCO3, SrCO3 and BaCO3). The effects of concentration catalyst (0.25 %w/w-1.5 %w/w) and molar ratio of methanol to oil (3:1-21:1) on biodiesel yield and conversion of FFA to FAME was investigated. From this study, SrCO3 gave better yields of FAME while CaCO3 gave better conversion of FFA to FAME. The lowest yield of FAME was recorded at catalyst concentration of 0.25 %w/w while the highest yield of FAME was at 1.25 %w/w. The lowest conversion of FFA to FAME was at 0.25 %w/w and the highest conversion at catalyst concentration of 0.75 %w/w. For the molar ratio of methanol to oil, the minimum yield of FAME at 21: while the maximum yield of FAME was obtained at 3:1. The minimum conversion of FFA to FAME was recorded at 3:1 molar ratio methanol to oil. However, maximum conversion was recorded at 15:1 molar ratio methanol to oil. This study revealed that biodiesel was successfully reduced 52.3 % opacity level of smoke emission by diesel engine that operated with petroleum diesel.